PENYULUHAN AKUNTANSI PERUSAHAAN JASA BAGI PARA SISWA YAYASAN PRIMA UNGGUL - Widjaja, Djeni Indrajati (Jurnal Serina Abdimas, 2025)
A service firm is one that offers services; its goods are non-tangible and include things like consultants, accounting offices, travel agency, movie theaters, and transportation companies. Just like with trading and industrial companies, accounting records are crucial for service companies as well. Data from the records are used to create five different types of financial reports: notes to the financial statements, profit and loss reports, financial position reports, equity reports, and cash flow reports. The students of the Prima Unggul Foundation who are educated to excel and be independent, in addition to studying in formal schools, also have several activities that require recording and are in contact with accounting, such as performing arts, making food/catering, motorbike washing services, gardening, etc. For this reason, this community service activity, namely providing counseling on accounting, will be very beneficial for them. This is because the accounting material they receive from the School is very little and does not describe an accounting cycle in a Company. The extension method for a material or object of discussion is chosen because it is a complete set of brief and complete descriptions or explanations of accounting activities in a company, with additional solutions to learning materials like this, The goal is for students to have a deeper understanding of accounting in a service organization. Considering the students' abilities, the outcomes of this extension may be deemed to be highly effective to answer the quizzes prepared by the resource person. ABSTRAK Perusahaan jasa adalah perusahaan yang menawarkan jasa; barang-barangnya tidak berwujud dan mencakup jasa seperti konsultan, kantor akuntansi, agen perjalanan, bioskop, dan perusahaan transportasi. Sama seperti perusahaan perdagangan dan industri, pencatatan akuntansi juga penting bagi perusahaan jasa. Data transaksi dicatat dan digunakan untuk membuat lima jenis laporan keuangan yang berbeda: catatan atas laporan keuangan, laporan laba rugi, laporan posisi keuangan, laporan ekuitas, dan laporan arus kas. Siswa/i Yayasan Prima Unggul yang dididik untuk unggul dan mandiri, selain berkegiatan belajar disekolah formal juga mempunyai beberapa kegiatan yang membutuhkan pencatatan dan bersentuhan dengan akuntansi, seperti misalnya melakukan pentas seni, membuat masakan/catering, kegiatan jasa cuci motor , berkebun, dan lainnya. Untuk itulah kegiatan pengabdian masyarakat ini yaitu memberikan penyuluhan tentang akuntansi akan sangat bermanfaat bagi mereka. Hal tersebut dikarenakan materi seputar akuntansi yang mereka terima dari sekolah sangat sedikit dan tidak menggambarkan suatu siklus akuntansi di suatu perusahaan. Metode penyuluhan untuk suatu materi atau objek bahasan dipilih karena merupakan suatu set utuh gambaran atau penjelasan singkat dan lengkap kegiatan akuntansi disuatu perusahaan, dengan solusi tambahan materi pelajaran seperti ini diharapkan para siswa dapat lebih memahami tentang akuntansi pada suatu perusahaan jasa. Hasil penyuluhan ini dapat dianggap cukup berhasil dengan melihat kemampuan siswa dalam menjawab kuis yang disiapkan nara sumber.